Role of AlGaN/GaN interface traps on negative threshold voltage shift in AlGaN/GaN HEMT. (April 2018) - Malik, Amit; Sharma, Chandan; Laishram, Robert; Bag, Rajesh Kumar; Rawal, Dipendra Singh; Vinayak, Seema; Sharma, Rajesh Kumar
Highlights: Role of AlGaN/GaN interface states in threshold voltage shift. Extraction of AlGaN/GaN interface states density and their time constant. Role of interface states is analyzed by TCAD ATLAS simulation. Abstract: This article reports negative shift in the threshold-voltage in AlGaN/GaN high electron mobility transistor (HEMT) with application of reverse gate bias stress. The device is biased in strong pinch-off and low drain to source voltage condition for a fixed time duration (reverse gate bias stress), followed by measurement of transfer characteristics. Negative threshold voltage shift after application of reverse gate bias stress indicates the presence of more carriers in channel as compared to the unstressed condition. We propose the presence of AlGaN/GaN interface states to be the reason of negative threshold voltage shift, and developed a process to electrically characterize AlGaN/GaN interface states. We verified the results with Technology Computer Aided Design (TCAD) ATLAS simulation and got a good match with experimental measurements.